Method for rapidly determining components of refining slag through X-ray fluorescence spectrometry

By combining X-ray fluorescence spectroscopy with chemical wet processing to treat refining slag, the problems of long analysis cycles, cumbersome operation and high cost in traditional methods are solved, and rapid and accurate refining slag composition analysis is achieved, which is suitable for batch analysis in steelmaking production.

CN120927723APending Publication Date: 2025-11-11WUYANG IRON & STEEL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511026598.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-24
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Traditional chemical wet methods and glass fusion X-ray fluorescence analysis methods have long analysis cycles, cumbersome operation, high reagent consumption, high labor intensity and difficulty in batch analysis. Moreover, after the application of new refining slag, the original slag analysis curves cannot cover the content range, which cannot meet the production needs of accurate analysis.

Method used

X-ray fluorescence spectroscopy combined with chemical wet method was used to process the refining slag sample. A standard curve was plotted using a self-made standard sample, and the sample was analyzed using an imported Shimadzu X-ray fluorescence spectrometer. The measurement conditions were optimized and the operation procedure was simplified to achieve rapid and accurate analysis.

Benefits of technology

It enables rapid batch analysis with short analysis cycle, low cost and good stability, meeting the rapid analysis needs of steelmaking production, reducing analysis costs and waste liquid discharge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a method for rapidly determining components of refining slag through X-ray fluorescence spectrometry, efficient detection of silicon dioxide, calcium oxide, magnesium oxide and aluminum oxide is realized through combination of chemical wet method valuing and optimization of sample preparation and instrument conditions, and the method specifically comprises the following steps: S1, taking a refining slag sample, crushing, and screening the refining slag sample with the particle size of not more than 180 meshes; s2, selecting a certain number of crushed and screened refining slag samples with different contents, and analyzing and valuing by using a chemical wet method to serve as standard samples; and S3, drawing a standard curve by utilizing the self-made standard sample, and measuring silicon dioxide, calcium oxide, magnesium oxide and aluminum oxide in the refining slag by utilizing X fluorescence. The method is short in analysis period, low in cost, good in stability and suitable for batch rapid analysis of the refining slag in steelmaking production, and the problems that a traditional method is low in efficiency and tedious in operation are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metallurgical chemical analysis technology, specifically relating to a method for rapid determination of the composition of refining slag by X-ray fluorescence spectrometry, the composition of which includes silicon dioxide, calcium oxide, magnesium oxide and aluminum oxide. Background Technology

[0002] Traditional chemical wet methods and glass flake X-ray fluorescence analysis have drawbacks such as long analysis cycles (over 6 hours per operation), cumbersome operation (requiring individual elemental analysis), high reagent consumption (more than 10 reagents per method), high labor intensity (requiring multiple people to collaborate), and difficulty in batch analysis. After the application of the new refining slag, the original slag analysis curves cannot cover the content range, failing to meet the production requirements for accurate analysis. Summary of the Invention

[0003] To address the aforementioned problems, the present invention aims to provide a rapid analytical method for refining slag, covering a wide range of content to meet the production requirements for accurate analysis, while also ensuring the stability of the analytical results obtained by this method.

[0004] The technical solution of this invention: A method for rapid determination of refining slag composition by X-ray fluorescence spectrometry includes the following steps: S1. Take a refined slag sample, crush it, and screen the refined slag sample with a particle size not exceeding 180 mesh. S2. Select a certain number of crushed and screened refining slag samples with different contents, and use chemical wet method to analyze and determine the values ​​as standard samples. S3. Using self-made standard samples, a standard curve was plotted, and X-ray fluorescence was used to determine the silica, calcium oxide, magnesium oxide, and aluminum oxide in the refining slag.

[0005] Preferably, the chemical wet method for analysis and determination in S2 specifically includes: determining the amount of silicon by perchloric acid dehydration gravimetric method, and determining the amount of aluminum oxide, calcium oxide, and magnesium oxide by EDTA complexation capacity method.

[0006] Preferably, the number of refining slag samples selected in S2 is not less than 9.

[0007] Preferably, the determination conditions for determining silica in refining slag using X-ray fluorescence in S3 are as follows: analytical line is Kα, tube voltage is 40 kV, tube current is 30 mA, crystal is LiF, detector is SPC, measurement time is 40 min, and pulse relative height is 16~86.

[0008] Preferably, the determination conditions for determining calcium oxide in refining slag using X-ray fluorescence in S3 are as follows: analytical line is Kα, tube voltage is 40 kV, tube current is 70 mA, crystal is TAP, detector is SPC, measurement time is 40 min, and pulse relative height is 25~85.

[0009] Preferably, the determination conditions for determining magnesium oxide in refining slag using X-ray fluorescence in S3 are as follows: analytical line is Kα, tube voltage is 40 kV, tube current is 70 mA, crystal is PET, detector is SPC, measurement time is 40 min, and pulse relative height is 25~85.

[0010] Preferably, the determination conditions for determining alumina in refining slag using X-ray fluorescence in S3 are as follows: analytical line is Kα, tube voltage is 40 kV, tube current is 70 mA, crystal is PET, detector is SPC, measurement time is 40 min, and pulse relative height is 34~86.

[0011] Preferably, the specific method for plotting the standard curve using self-made standard samples in S3 is as follows: under the selected measurement conditions, the X-ray fluorescence intensity of the standard series sample pieces is measured separately. Two sets of samples are prepared independently for the standard series sample pieces. The average value of the measured X-ray fluorescence intensity is taken, and a working curve of intensity versus content is established using a regression analysis program.

[0012] Preferably, the method for preparing the refining slag sample for X-ray fluorescence determination in S3 is as follows: a polyvinyl chloride ring with an inner diameter of 35 mm and a height of 4 mm is selected as the compression ring. The sample is determined to pass through a 220-mesh standard sieve through a particle size test. The sample weight, pressure, and static pressing time are determined to be 8 g, 45 T, and 20 s, and the sample is pressed once before testing.

[0013] This invention provides an operational method that facilitates routine analysis in daily production, enabling samples to be tested as soon as they arrive, thus meeting the fast-paced production needs of steelmaking furnaces.

[0014] We used wet chemistry to determine the elemental values ​​of selected refining slag samples with a certain content gradient, and established an analytical method for refining slag using an imported Shimadzu X-ray fluorescence spectrometer.

[0015] Operators using the technology of this invention should have a certain level of expertise in instrumentation and chemical analysis to ensure the stability and accuracy of the analytical results.

[0016] The beneficial effects of this invention are: This invention features a short analysis cycle, low cost, and good stability, making it suitable for rapid batch analysis of refining slag in steelmaking production. It solves the problems of low efficiency and cumbersome operation associated with traditional methods.

[0017] This invention utilizes a chemical wet process to determine the values ​​of silica, calcium oxide, magnesium oxide, and aluminum oxide in steelmaking refining slag. An analytical method is established on an X-ray fluorescence emission spectrometer to analyze silica, calcium oxide, magnesium oxide, and aluminum oxide, thereby reducing analysis costs, shortening the analysis cycle, and reducing waste liquid discharge.

[0018] This invention provides a rapid analytical method for refining slag, covering a wide content range to meet the production requirements for precise analysis. Furthermore, the analytical results obtained by this method exhibit good stability. This invention is applicable to the analysis of refining slag, but not to the analysis of steelmaking slag or continuous casting mold flux. Detailed Implementation

[0019] Specific implementation steps of the present invention I. Sampling Requirements: Sampling shall be carried out in accordance with production requirements, and the particle size of the sample shall be less than 180 mesh.

[0020] II. Fixed value method: Refining slag is a composite material made from several materials, and the proportions vary from plant to plant. Since there are no standard samples available for the refining slag system currently in use, samples with different concentrations of 9 were selected at different times based on the structure and composition of the refining slag. Values ​​were determined using traditional chemical analysis, and a series of internal control standard samples were prepared. The values ​​of the internal control standard samples are shown in Table 1.

[0021] Determination of silicon content by perchloric acid dehydration gravimetric method: Clean the nickel crucible and place it in a beaker containing water [add a small amount of hydrochloric acid (ρ 1.19 g / ml)]. Boil, then clean again and evaporate to dryness on an electric furnace. Add 2 g of sodium hydroxide (solid) to the bottom for dehydration, then heat and gently shake to spread evenly on the bottom of the nickel crucible. After solidification, weigh 0.5000 g of the sample. Add approximately 2 g of sodium hydroxide to cover the sample (leaving a gap in the lid), and place in a muffle furnace at 750℃. Melt for 15 minutes and remove. After removing the sample, rotate the crucible to allow the melt to adhere to the inner wall of the crucible, and allow it to cool. Rinse the outer wall of the crucible and immerse it in a 300 ml beaker, washing with hot water until clean. (Keep the washing volume as small as possible) Add 30 ml of hydrochloric acid (ρ 1.19 g / ml) and heat until the sample is completely dissolved (add more hydrochloric acid as needed if necessary). (For remelted slag and low-carbon slag, add two spoonfuls of boric acid). After the sample is concentrated, add 40 ml of perchloric acid, cover with a watch glass, and heat to evaporate until thick white fumes are emitted, until the residue is pasty and nearly dry. Remove and cool, add 10 ml of hydrochloric acid (1+1) along the wall, add 100 ml of hot water to rinse the watch glass and the glass wall, and stir to dissolve the salts. While hot, filter through medium-speed quantitative filter paper (with pulp) into a 500 ml volumetric flask and receive (as the test solution "A"). Wash the beaker with hot hydrochloric acid (5+95) washing solution, wash the precipitate until no iron ions are present (test with ammonium thiocyanate solution), and then wash with hot water until no chloride ions are present (test with silver nitrate solution). The precipitate, along with the filter paper, is placed in a porcelain crucible. The moisture is first evaporated at a low temperature, then ashed at a high temperature, and then ignited in a muffle furnace at 1000℃ for 50 minutes. After being slightly cooled, it is placed in a desiccator to cool to room temperature and weighed to obtain (G1). The silicon content is then calculated according to the formula.

[0022] Determination of aluminum oxide by EDTA complexometric titration: Pipette 50 mL of the test solution "A", add 50 mL of water, add 20-30 mL of EDTA (0.01 mol / L); add 1 drop of methyl orange indicator (0.1%), adjust the solution with ammonia (1+1) until the red just turns yellow, add 20 mL of buffer solution (pH=5.6). Heat to boiling for at least 3 minutes, cool under running water to room temperature, add 3 drops of xylenol orange indicator (0.5%), titrate with zinc acetate solution (0.01 M / L) until the test solution changes from yellow to red (do not count), then add 1 g of ammonium fluoride solid, heat to boiling for at least 3 minutes, cool under running water to room temperature, add 10 mL of buffer solution (pH=5.6), add 2 drops of xylenol orange indicator (0.5%), titrate with zinc acetate standard solution (0.01 M / L) until the solution changes from yellow to red, and record the scale reading. The aluminum oxide content was calculated using the formula.

[0023] Determination of calcium oxide and magnesium oxide by EDTA complexometric titration: Pipette 100 ml of the test solution "A" into a 250 ml beaker, adjust the pH to near 7 with ammonia water (1+1), add 5 ml of hexamethylenetetramine (10%) and 10 drops of bromine water. Heat to boiling, cool to room temperature, transfer to a 250 ml volumetric flask containing 2 g of copper reagent, dilute to the mark and shake well. After the precipitate settles (and stands for 2 hours), filter the filtrate and collect it in a 250 ml beaker as test solution "B". Determination of CaO: Pipette 50 ml of test solution "B" into a 250 ml beaker, add 1-2 ml of magnesium reagent, add 30 ml of water and 10 ml of triethanolamine (1+1), shake well, add 20 ml of sodium hydroxide solution (20%), add a small amount of calcium indicator, and titrate with EDTA (0.01 mol / L) standard solution until the test solution changes from red to the endpoint, and record the volume in milliliters. Determination of MgO: Pipette 50 ml of the test solution "B" into a 250 ml beaker, add 30 ml of water and 10 ml of triethanolamine (1+1), shake well, add 20 ml of ammonia buffer solution (pH=10), add a small amount of Eriochrome Black T indicator, and titrate with EDTA (0.01 mol / L) standard solution until the test solution changes from red to the endpoint, and record the volume in milliliters. Calculate the content of calcium oxide and magnesium oxide according to the formula.

[0024] Table 1. Content of each component in the internal control standard sample of refining slag

[0025] Third, by using self-made standard samples to plot working curves on an X-ray fluorescence spectrometer, the sample can be processed simply and the analytical results can be obtained accurately and promptly using X-ray fluorescence spectroscopy.

[0026] 3.1 Instruments and Reagents XRF-1800X fluorescence spectrometer (Shimadzu Corporation, Japan), powder compactor (Shimadzu Corporation, Japan), PR gas (90% argon + 10% methane).

[0027] 3.2 Instrument measurement conditions: Select the final measurement conditions according to the instrument manual, as shown in Table 2.

[0028] Table 2 Measurement conditions

[0029] PET—Polyethylene terephthalate crystals; TAP—Thallium hydrogen phthalate crystals; SPC—Sealed gas proportional counter detector 3.3 Sample Preparation A polyvinyl chloride ring with an inner diameter of 35 mm and a height of 4 mm was selected as the tablet compression ring. Through particle size test, it was determined that the sample could pass through a 220-mesh standard sieve. Through sample weight, pressure, and static pressing time test, it was determined that the sample weight was 8 g, the pressure was 45 T, and the static pressing time was 20 s. The sample was pressed once and then tested.

[0030] 3.4 Working Curve Under the selected measurement conditions, the X-ray fluorescence intensity of the standard series samples was measured separately. Two sets of samples must be prepared independently for the standard series samples. The average value of the measured X-ray fluorescence intensity was taken and entered into the computer program. The regression analysis program was used to establish the working curve of intensity versus content. The empirical coefficient method was used to correct for inter-element interference and calculate the correction coefficient.

[0031] 3.5 Measurement Place the prepared sample into the sample box, and then place the sample box into the sample turntable. Start the "X-ray Fluorescence Analysis Main Program," select the "Daily Analysis" mode and the corresponding database. Enter the sample number, place the sample in the box, and start the detection. The results are automatically saved to the database and printed out.

[0032] 3.6 Precision and Accuracy Experiment 3.6.1 Precision Experiment Take a sample of refining slag, prepare 10 sample pieces according to the sample preparation requirements, and use the established quantitative analysis procedure to measure the 10 sample pieces, calculate the average value and standard deviation of each element, and the results are shown in Table 3.

[0033] Table 3 Precision Experiment (n=10)

[0034] 3.6.2 Accuracy Experiment To obtain accurate analytical results, we used two samples and analyzed them using standard chemical analysis methods. We then compared the chemical analysis results with those obtained by X-ray fluorescence analysis. The results are shown in Table 4.

[0035] Table 4 Comparison of Analysis Results

[0036] The contents of major chemical components such as SiO2, Al2O3, CaO, and MgO in refining slag were determined by X-ray fluorescence spectrometry. Curves were plotted using self-made standards, and spectral interference and matrix effect correction coefficients were employed to eliminate spectral interference and matrix effects. Experimental results show that this method is simple, rapid, and has good precision and accuracy. The results obtained are consistent with those obtained by wet chemical analysis, providing timely analytical data that meets current production requirements.

[0037] In actual production, this invention can be implemented using the following methods: 1. Sample Preparation: Take samples according to production requirements. When grinding, add approximately 80 grams of sample and grind for 90 seconds to prepare an analytical sample with a particle size of less than 180 mesh. Place the sample into an iron sample cup, put it in a sample press, and press it under 40 tons of pressure for 30 seconds to prepare a sample sheet.

[0038] 2. Sample Analysis: Start the "X-ray Fluorescence Analysis Main Program", select the "Daily Analysis" mode and the corresponding database. Enter the sample number, place the sample slide, and start the detection. The results will be automatically saved to the database.

[0039] 3. Accuracy verification: Regularly compare the results with chemical analysis results to ensure the accuracy of instrument analysis.

[0040] It should be noted that operators using this invention should possess relevant professional knowledge of chemical analysis and understand common safety procedures in chemical analysis. This invention is applicable to the simultaneous determination of various components in refining slag. This invention uses an imported sample press to compress the analytical sample into a sample suitable for fluorescence analysis, resulting in low material consumption and low analysis costs. When using this invention, the results can be periodically compared with those of chemical analysis to verify the accuracy of the instrument's analytical operation.

[0041] Finally, it should be noted that the above embodiments are only used to illustrate and not limit the technical solutions of the present invention. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the present invention without departing from the spirit and scope of the present invention. Any modifications or partial substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A method for rapid determination of refining slag composition by X-ray fluorescence spectrometry, characterized in that, Includes the following steps: S1. Take a refined slag sample, crush it, and screen the refined slag sample with a particle size not exceeding 180 mesh. S2. Select a certain number of crushed and screened refining slag samples with different contents, and use chemical wet method to analyze and determine the values ​​as standard samples. S3. Using self-made standard samples, a standard curve was plotted, and X-ray fluorescence was used to determine the silica, calcium oxide, magnesium oxide, and aluminum oxide in the refining slag.

2. The method for rapid determination of refining slag composition by X-ray fluorescence spectrometry according to claim 1, characterized in that, The chemical wet method described in S2 specifically involves: determining the amount of silicon by perchloric acid dehydration gravimetric method, and determining the amount of aluminum oxide, calcium oxide, and magnesium oxide by EDTA complexation capacity method.

3. The method for rapid determination of refining slag composition by X-ray fluorescence spectrometry according to claim 1, characterized in that, The number of refining slag samples selected in S2 shall not be less than 9.

4. The method for rapid determination of refining slag composition by X-ray fluorescence spectrometry according to claim 1, characterized in that, The determination conditions for silicon dioxide in refining slag using X-ray fluorescence in S3 were as follows: analytical line Kα, tube voltage 40 kV, tube current 30 mA, crystal LiF, detector SPC, measurement time 40 min, and pulse relative height 16–86.

5. The method for rapid determination of refining slag composition by X-ray fluorescence spectrometry according to claim 1, characterized in that, The determination conditions for calcium oxide in refining slag using X-ray fluorescence in S3 were as follows: analytical line Kα, tube voltage 40 kV, tube current 70 mA, crystal TAP, detector SPC, measurement time 40 min, and pulse relative height 25–85.

6. The method for rapid determination of refining slag composition by X-ray fluorescence spectrometry according to claim 1, characterized in that, The determination conditions for magnesium oxide in refining slag using X-ray fluorescence in S3 were as follows: analytical line Kα, tube voltage 40 kV, tube current 70 mA, PET crystal, SPC detector, measurement time 40 min, and pulse relative height 25–85.

7. The method for rapid determination of refining slag composition by X-ray fluorescence spectrometry according to claim 1, characterized in that, The determination conditions for alumina in refining slag using X-ray fluorescence in S3 were as follows: analytical line Kα, tube voltage 40 kV, tube current 70 mA, PET crystal, SPC detector, measurement time 40 min, and pulse relative height 34–86.

8. The method for rapid determination of refining slag composition by X-ray fluorescence spectrometry according to claim 1, characterized in that, The specific method for plotting the standard curve using self-made standard samples in S3 is as follows: Under the selected measurement conditions, the X-ray fluorescence intensity of the standard series sample pieces is measured separately. Two sets of samples are prepared independently for the standard series sample pieces. The average value of the measured X-ray fluorescence intensity is taken, and a working curve of intensity versus content is established using a regression analysis program.

9. The method for rapid determination of refining slag composition by X-ray fluorescence spectrometry according to claim 1, characterized in that, The preparation method for the X-ray fluorescence determination of refining slag in S3 is as follows: a polyvinyl chloride ring with an inner diameter of 35 mm and a height of 4 mm is selected as the compression ring. Through particle size test, it is determined that the sample can pass through a 220-mesh standard sieve. Through sample weight, pressure and static pressing time test, it is determined that the sample weight is 8 g, the pressure is 45 T and the static pressing time is 20 s. The sample is pressed once and then tested.